Pelatihan Pengenalan Teknologi san Digitalisasi untuk Bisnis UMKM - Prasetyo, Johan Hendri; Fabrianto, Luky; Wiharso, Gani; Puspita, Ratna (Jurnal Abdimas Perbanas, 2025)
In today’s fast-paced digital era, MSMEs in Bekasi City face significant challenges in integrating digital technology into their business operations. Many lack the knowledge and skills needed to adopt technology effectively, making them vulnerable to competitive disadvantages, limited market expansion, and exposure to digital security threats. To address these issues, comprehensive digital literacy training is essential to empower MSME actors to utilize technology in a safe and efficient manner that supports business growth. The "Introduction to Technology and Digitalization for MSME Businesses" training program is designed to equip participants with foundational knowledge of computers and the internet, effective use of social media as a marketing tool, and the basics of digital security to safeguard business information. By participating in this program, MSME actors from the UMKM Naik Kelas community in Bekasi are expected to improve their ability to adopt digital solutions, expand market reach, and enhance competitiveness. This initiative aims to produce tangible outcomes, including increased understanding of digital tools, practical application of social media for business promotion, and heightened awareness of cybersecurity measures. These skills will enable MSME actors to modernize their operations, better integrate technology, and ultimately strengthen their business resilience and economic contributions. With enhanced digital capabilities, MSMEs can achieve sustained growth, reinforce their presence in the marketplace, and contribute more effectively to local economic development.